A nonlinear parabolic equation with drift term. (December 2018) - Farroni, Fernando; Moscariello, Gioconda
Abstract: We consider weak solutions to a nonlinear evolution diffusion–convection equation with an unbounded convection field. We provide existence and uniqueness results as well as the asymptotic behaviour of solutions.